Ответы и объяснения

Лучший Ответ!
  • AlbuRin
  • светило науки
2013-06-30T03:01:30+00:00

a)      y=2x^3-x^1/4-cos2x

         y " = (2x^3 -x^1/4 -cos2x) "  =  (2x^3) " - (x^1/4) " -(cos2x) "   =

         =2*3x^(3-1)  -1/4x^(1/4 - 1) - (-sin2x) * (2x) "  =  6x^2  -1/4x^(-3/4)  +sin2x * 2  =

         =6x^2   -   1 : (4x^3/4)  +  2sin2x

 

b)      y = sin(8x^3 - 9x)

          y " =  (sin(8x^3-9x) "  =  cos(8x^3-9x) * (8x^3 - 9x) "  =  cos(8x^3-9x) * (24x^2 -9)  =

               = (24x^2 - 9) * cos(8x^3 - 9x)